2021
DOI: 10.3390/jcm10112507
|View full text |Cite
|
Sign up to set email alerts
|

A Multidisciplinary Approach to Evaluate the Presence of Hepatic and Cardiac Abnormalities in Patients with Post-Acute COVID-19 Syndrome—A Pilot Study

Abstract: (1) Background: Patients suffering from the novel coronavirus 2019 (COVID-19) disease could experience several extra-pulmonary involvements, including cardiovascular complications and liver injury. This study aims to evaluate the presence of cardiac and liver alterations in patients with post-acute COVID-19 syndrome using transthoracic echocardiography (TTE) and liver elastography (LE). (2) Methods: A total of 97 subjects recovering from COVID-19, attending the hospital’s specialized outpatient clinic for pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 37 publications
0
26
0
Order By: Relevance
“…Likewise, other complications have been reported, such as postural orthostatic tachycardia syndrome [81,82] and orthostatic intolerance without hemodynamic effects [83]. Lastly, right ventricular dysfunction in response to fibrotic lung injury, pulmonary hypertension and/or clot burden in patients recovering from severe disease have also been described with an incidence of diastolic dysfunction of 32-55%, and an occurrence of pulmonary hypertension of 10-35% up to 12 weeks following the acute phase [84][85][86].…”
Section: Cardiovascular Involvementmentioning
confidence: 98%
“…Likewise, other complications have been reported, such as postural orthostatic tachycardia syndrome [81,82] and orthostatic intolerance without hemodynamic effects [83]. Lastly, right ventricular dysfunction in response to fibrotic lung injury, pulmonary hypertension and/or clot burden in patients recovering from severe disease have also been described with an incidence of diastolic dysfunction of 32-55%, and an occurrence of pulmonary hypertension of 10-35% up to 12 weeks following the acute phase [84][85][86].…”
Section: Cardiovascular Involvementmentioning
confidence: 98%
“…However, in contrast with Deffieux’s study, viscosity was found to be useful for predicting the degree of necroinflammation [ 16 , 31 ]. Moreover, a recently published study found higher Vi PLUS liver values in COVID-19 patients with pulmonary injury compared to COVID-19 patients without pulmonary injury [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, elevated baseline AST especially in patients aged > 65 years was a strong predictor of adverse clinical outcomes. Recently, LSM and CAP were also investigated among patients with persisting post-acute COVID-19 syndrome and no history of liver disease [35]. LSM but not CAP was higher (but still within the normal range) in patients who suffered from a more severe form of COVID-19 during acute illness (5.08 kPa vs. 4.39 kPa, p = 0.017 for LSM, and 291.64 dB/m vs. 266.06 dB/m, p = 0.062 for CAP).…”
Section: Discussionmentioning
confidence: 99%